Independent Living Skills Taught and Vocational Training Trades/Facilities Available for Students with Intellectual Disabilities at Schools - Farhat Munir; Dr. Muhammad Javed Aftab; Sadia Batool; Robina Naqvi; Navid Ur Rehman (Al-Qanṭara, 2023)
This article investigates the independent living skills and vocational training opportunities for students with intellectual disabilities, particularly in Pakistan, where around 2.49% of the population has disabilities. The primary objective is to evaluate the effectiveness of training and support programs in facilitating the integration of individuals with intellectual disabilities. The findings emphasize the significance of personalized training and support in enhancing the skills of individuals with intellectual disabilities. However, challenges persist in providing inclusive educational environments and equitable skill development opportunities. This study underscores the urgent need for unwavering commitment to inclusive policies, particularly for school-going children with disabilities. In conclusion, the research advocates for the development of tailored career pathways and strengthened inclusive policies to empower individuals with intellectual disabilities, taking into account the unique challenges they face, including factors related to disability and gender disparities.